Exploring brand trust, experience, and repurchase intention in halal fashion: The role of e-WOM - Adha, Mufti Alam; Inda Lestari; Nahar, Faiza Husnayeni (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examines how brand trust, experience, and repurchase intention affect halal fashion purchase decisions mediated by electronic word of mouth (e-WOM)Methodology – This study employs survey data from 198 respondents using the Elzatta brand. Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach was used, and purposive sampling was applied.Findings – The findings of this study suggest that brand experience and repurchase intention significantly influence e-WOM and purchase decisions both directly and through mediation. By contrast, brand trust has a negative and insignificant effect on e-WOM and mediates purchase decisions.Implications – This study is useful for improving marketing strategies by strengthening brand trust, enhancing brand experience, and leveraging digital word of mouth to support consumer purchase decisions.Originality – This study contributes to the scholarly discourse on consumer behavior in the halal fashion sector by elucidating the mediating role of electronic word of mouth (e-WOM) in the relationship between brand trust, brand experience, and repurchase intention and purchase decisions. Thus, this study offers both managerial and theoretical insights.